FAILURE TO VISUALIZE A MULTICYSTIC KIDNEY WITH TECHNETIUM 99M-DTPA DOES NOT PRECLUDE RECOVERABLE FUNCTION - Taher, M. A. (The ASEAN Journal of Radiology, 2023)
We present a patient with multicystic left kidney as diagnosed by ultrasonography. 99m Tc-DTPA scintigram showed absent uptake by the left kidney, however, post-operative scan after partial nephrectomy was normal. In this case, absence of 99m Tc-DTPA uptake by the kidney does not necessarily mean that renal function 1s irreversibly lost in a patient with multiple cysts.